Does applying design thinking result in better new product concepts than a traditional innovation approach? An experimental comparison study. Issue 4 (August 2020) - Meinel, Martin; Eismann, Tobias T.; Baccarella, Christian V.; Fixson, Sebastian K.; Voigt, Kai-Ingo
Abstract: Both practitioners and researchers have developed various approaches to support product development teams in their creative process of generating new and valuable product concepts. A key concern of all innovation approaches is to translate the needs, wants and aspirations of users and customers into product and service solutions that match the underlying needs. Many existing innovation approaches focus predominantly on the translation process itself by providing support for aggregating data and making trade-off decisions between user preferences traceable. For that reason, we label these approaches user preference-driven. In contrast, over the last two decades, design thinking (DT) has emerged as an approach that assumes knowledge of user needs information to be fuzzy and unreliable; it addresses this challenge by focusing on developing user experiences through empathic in-depth user research and iterative prototyping. Consequently, we label approaches such as DT user experience-driven. Although DT has generated particular interest among both practitioners and educators, the academic literature investigating the usefulness of DT remains scarce. To help close this gap, we study the performance implications of applying DT processes and tools in terms of new product concept creativity relative to applying a traditional innovation approach. Using an experimental design and collecting quantitative data from 53 teams and their projects, we find that teams applying DT outperform the control group that applies an alternative innovation approach, namely quality function deployment (QFD), in terms of the feasibility, relevance and specificity of concepts, but not the novelty. We discuss the implications of our findings for theory and practice.